An Analysis of Three Dimensional Aspects Reflected in the Movie Entitled “Barbie” - Kania Maharani, Ni Putu; Gde Nova Winarta , Ida Bagus (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
The study focused ot find out three dimensional aspects in the movie entiled Barbie (2023). The movie produced by Greta Gerwig and written by Noah Baumbach. The story is about the stereotypical Barbie as a fellow dolls resident in Barbieland. She lives with Ken and other differents barbie dolls. Then, while kens spend their playing at the beach, considering it their profession, the Barbie hold prestigious job such as doctor. Beach Ken (